Long-term functional swallowing and speech outcomes after transoral robotic surgery for oropharyngeal cancer - Ji, Yong Bae; Choi, Hae Won; Song, Chang Myeon; Yun, Bo Ram; Park, Hae Jin; Oh, Sukjoong; Tae, Kyung (Frontiers in Surgery, 2024)
Objectives Transoral robotic surgery (TORS) has emerged as a minimally invasive approach for oropharyngeal cancer, aiming to improve functional preservation and reduce morbidity. However, the long-term effects on speech and swallowing, crucial aspects of quality of life, remain unclear. This study investigates the long-term functional swallowing and speech outcomes of TORS for oropharyngeal cancer. Methods We retrospectively reviewed 41 patients diagnosed with oropharyngeal squamous cell carcinoma who underwent TORS from 2010 to 2018. Tongue mobility, articulation, verbal diadochokinesis, reading speed, and modified barium swallowing tests were performed 2–3 years post-operatively to assess long-term speech and swallowing function. Results The mean age was 57.7 ± 9.9 years, and the male to female ratio was 34:7. The palatine tonsil was the most common tumor site (73.2%), followed by the base of tongue (22.0%). Concurrent neck dissection was performed in 97.6% of patients, and adjuvant radiation or chemoradiation was administered to 36 patients (87.8%). Tongue mobility, articulation, verbal diadochokinesis, and reading speed were comparable to normal population. Modified barium swallowing tests revealed acceptable outcomes in most patients; only one patient (2.4%) required a percutaneous endoscopic gastrostomy tube. Notably, no permanent tracheostomies were necessary. Conclusions Long-term speech and swallowing functions were preserved in most patients treated with TORS for oropharyngeal cancer. TORS is an excellent treatment modality for oropharyngeal cancer in terms of functional outcomes.